The Other Side of Forrest Gump: Bernie Sanders (AmeriQuests, 2022)
The fictional Forrest Gump and Senator Bernie Sanders share more similarities than one may realize. This cinematic cultural heritage can aid us in understanding our future, especially when looking towards progressive politics.